Ide Mengatasi Food Waste dalam Sistem Food & Beverage Hotel: Perspektif Ketidaksesuaian Sistem - Firmansyah Firmansyah; Kris Cahyani Ermawati; Alip Suroto (Jurnal Ekonomi, Manajemen Pariwisata dan Perhotelan, 2026)
This study aims to analyse the generation of food waste in the operations of the Food & Beverage Department at Hotel Neo Malioboro, Yogyakarta, and to formulate a conceptual model for its management based on the food waste hierarchy and the 3R strategy. This study employs a qualitative approach using a single-case study design, involving in-depth interviews, participatory observation and documentation, which were analysed using thematic coding techniques through the stages of open, axial and selective coding. The results of the study indicate that food waste is generated systematically as a result of a lack of synchronisation between operational processes within the Food & Beverage Department, influenced by forecasting errors, overproduction, the buffet system, and weak integration of the waste management system. Furthermore, the implementation of the food waste hierarchy and the 3R strategy was found to remain largely normative and not yet integrated into the hotel’s operational system, resulting in waste management that tends to be reactive. This study has produced a conceptual model explaining that food waste is generated through a systemic process that begins with sustainable hospitality, followed by system misalignment, ultimately resulting in food waste formation, which is reinforced by a multi-level causal structure and hierarchical implementation gaps. The main contribution of this study is the development of a theoretical extension in the form of an integrated operational system model for food waste management in the hospitality industry. These findings have important implications for strengthening data-driven operational management systems to support sustainable practices in the Food & Beverage sector.